2020
DOI: 10.5194/hess-24-1677-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the assimilation of environmental tracer observations for model-based decision support

Abstract: It has been advocated that history matching numerical models to a diverse range of observation data types, particularly including environmental tracer concentrations and their interpretations and derivatives (e.g., mean age), constitutes an effective and appropriate means to improve model forecast reliability. This study presents two regionalscale modeling case studies that directly and rigorously assess the value of discrete tritium concentration observations and tritium-derived mean residence time (MRT) esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…This insight agrees with Knowling et al. (2020) who suggest calibrating against tritium observations can deteriorate model performance when model structural error is large. Model structural errors cause the calibration to compensate through estimation of effective model parameters, which can be differ widely from the modeler's a priori expectation of reasonable parameter values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This insight agrees with Knowling et al. (2020) who suggest calibrating against tritium observations can deteriorate model performance when model structural error is large. Model structural errors cause the calibration to compensate through estimation of effective model parameters, which can be differ widely from the modeler's a priori expectation of reasonable parameter values.…”
Section: Discussionsupporting
confidence: 90%
“…Common ways to numerically simulate groundwater age include particle tracking methods (e.g., LaBolle et al., 1996; Pollock, 2012) or the transport of age mass using the advection‐dispersion equation (Ginn, 1999; Goode, 1996; Varni & Carrera, 1998). Particle tracking ages that only account for advective transport have been compared to groundwater ages that assume piston flow (Portniaguine & Solomon, 1998; Reilly et al., 1994; Sturchio et al., 2014; Szabo et al., 1996) or mean ages inferred using LPM (Gusyev et al., 2014; Knowling et al., 2020). Alternatively, groundwater mean age simulated with random walk particle tracking methods or the advection‐dispersion equation include dispersion‐based mixing processes and are expected to better correspond to mean ages of samples that are characterized by an age distribution (Gardner et al., 2015; Kolbe et al., 2016; Weissmann et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers in hydrological sciences have taken on the question of worth of data in recent years (e.g., Cirpka et al 2004; Fu and GĂłmez‐HernĂĄndez 2009; Dausman et al 2010; Wöhling et al 2016; Siade et al 2017; Sreekanth et al 2017; Knowling et al 2020). Tangentially, data worth estimation is often linked to the topic of monitoring network design, which includes the costs of potential measurements as well (e.g., Erickson et al 2002; Feyen and Gorelick 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Surrogate models is a term that encompasses a multitude of simplification‐methods and stand‐ins, with the common goal to “increase computational efficiency” (Asher et al 2015). Usually, they are divided in three distinct categories (cf Asher et al 2015): projection‐based methods (e.g., Vermeulen et al 2004a; McPhee and Yeh 2008; Pasetto et al 2013; Boyce and Yeh 2014; Ushijima and Yeh 2015; Stanko et al 2016), data‐driven methods (e.g., Khu and Werner 2003; Yoon et al 2011; Taormina et al 2012; Roy et al 2016; Fan et al 2020; Yin and Tsai 2020), and structural simplification methods (e.g., Sun 2008; Doherty and Christensen 2011; Watson et al 2013; von Gunten et al 2014; Knowling et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, this can compromise the reliability of decisions made on the basis of model forecasts. Additionally, Knowling et al (2020) showed that there is significant potential to induce predictive bias due to the inability of an imperfect model to appropriately assimilate information-rich data, such as environmental tracer observations. Therefore, when faced with using a model with prediction relevant imperfections, a modeler may wish to critically consider whether history matching is appropriate.…”
Section: Introductionmentioning
confidence: 99%